Pembuatan dan Pemanfaatan Dashboard Data Rekam Medis Sebagai Alat Bantu Sistem Pendukung Keputusan - Yuli Mardi; Annisa Wahyuni; fajri gusnil (Puslitbang Sinergis Asa Professional, 2023)
The implementation of a hospital management information system at the 'Aisyiyah Padang public hospital opens opportunities for academics to conduct research and experiments. The amount of data stored in the information system database can be used as an alternative for decision making by hospital management, including medical record data for patients who go to the hospital. Existing medical record data can be summarized and presented visually in the form of a dashboard according to the needs of the hospital. Dashboard can provide an overview to management to determine future policies or as a decision support system. This study aims to create a dashboard that can be used as a decision support system. This type of research is descriptive with the subject of medical record data in the database. From the research that has been done, it is found that the number of outpatient patients in 2021 is 23,635 patients. Of this number, the 3 insurers for the most patients were the Badan Penyelenggara Jaminan Sosial (BPJS) with 19,834 patients, Umum with 3,551 patients and Smile Train with 69 patients. For the 3 doctors who treat the most patients, Dr. Lisa Oktamuva, Sp.PD as many as 3284 patients, dr. Yanasta Moendanoe, Sp.OG with 3112 patients, and drg. Harfindo Nismal, Sp.BM as many as 2351 patients. From the research that has been done, it can be concluded that the designed dashboard is still simple and incomplete. From the dashboard it was also found that the person who is responsible for the most patients is BPJS and the doctor who serves the most patients is Dr. Lisa Oktamuva, Sp.PD.)